Stroke nurse compliance with assessment standards is enhanced by reducing the documentation burden: An implementation science study. - Perera, Anjali; Smith, Lisa; Garza, Brianna; Stout, Donald; Bashir, Moez M. I.; Allen, Samanta; Salter, Amber; Olson, DaiWai M. (Nursing Management, 2026)
Background: Implementation research is focused on identifying barriers and facilitators to adopting evidence-based practices. Measuring pupil activity with a quantitative pupillometer (QP) has been repeatedly demonstrated to be a more evidence-based than subjective assessment of pupil reactivity. Yet, despite global availability, QP adoption is inconsistent. A possible influencing variable is documentation burden. Purpose: The purpose of this study is to explore whether technology that provides for automated documentation is a facilitator for implementing QP. Methods: This institutional review board-approved study explored data that were documented manually (manual cohort) and data that were directly uploaded into the electronic health record (automated-upload cohort). Compliance with the unit-based policy for pupil assessment was determined for each 4-hour period of time during the patient's stay in the intensive care unit. Results: There were no significant demographic differences between the 122 manual-entry cohort and 229 automated-entry cohort patients. The mean compliance in the automated-entry cohort of 65.0% (95% CI: 61.6-68.4%) was significantly higher than the mean compliance in the manual-entry cohort (47.7% [95% CI: 43.7-51.8%]; t = -6.42, P < 0.0001). Implications: A reduced documentation burden is associated with increased adoption of an evidence-based practice.